The Qur`anic approach on science as source of ideas and research motivation - Shogar, Ibrahim (International Institute Of Islamic Thought And Civilization (ISTAC), 2011)
The main objective of this study is reflection on the Qur`anic approach on science. However, the focus point is to introduce the vital role of scientific discourse in the Qur`an on research motivation. The scientific spirit in Islam today, once again, needs reactivation for investigation in natural and human phenomena. The author holds the view that motivation for research is a subject matter of worldview, which is originally articulated by elements of the religion and culture. The Holy Qur`an presents scientific knowledge in various forms, such as general principals, systemization, and inspiring concepts; and some detailed information. Both, the analytical method of modern science and classical approach of early Muslim intellectuals are utilized in this research. The careful examination of the subject has concluded that maintaining peace, satisfying the basic needs of researchers, and eradication of poverty; are important aspects of research motivation. However, the most strategic factor, in the case of Muslim communities, is mobilization of the spiritual power that provided by the religious sources. The Qur`anic approach on science must utilized to create research spirit on Muslim scientist and scholars. This conclusion was based on many factors: including the fact that the starting point of the Holy Qur`an was revealed for first time in pre-Islamic society of Jahiliyyah, was reconstruction of the worldview and creation of curiosity and creative mind. Secondly; many philosophers of science are deeply aware of religious role on scientific research. For instance, the eminent mind of the modern science, Albert Einstein said: science can be created only by those who are thoroughly imbued with the aspiration toward truth and understanding, and such feelings lies in the sphere of religion.